Unlocking Library Potential: Insights into First-Year Undergraduate Students’ Participation in Library User Education and Their Perceptions of University Libraries - Kibos, Jane Chepkurui; Nkoroi , Lilian; Kerandi, Daniel Ongeri (International Journal of Professional Practice, 2025)
In contemporary learning environments, effective library user education is crucial for enhancing undergraduate students’ engagement and perception of library services. The world has witnessed rapid technological advancements, information digitization and increased availability of e-resources. Effective participation of the new library clientele in user education has become increasingly crucial in enabling students to navigate and utilize library resources. Despite these advancements, the university libraries in Meru County, Kenya, have experienced suboptimal usage, potentially due to students’ perceptions of the library. The study investigates the role of undergraduate students’ participation in library user education programs on the perceptions of library. The study was conducted in Meru County, focusing on two chartered universities: Kenya Methodist University (KeMU) and Meru University of Science and Technology (MUST). The study used descriptive survey design to collect data. The target population was 6138 first-year undergraduate students enrolled in the 2023/2024 academic year. The study employed stratified sampling techniques based on academic schools, and used the Krejcie and Morgan table to determine the sample size, which was 364 students. The researcher purposively sampled a total of 12 out of 46 library staff. Data was collected using questionnaire and interview schedule for the library staff. The study employed descriptive statistics, such as frequencies, percentages, means, and standard deviations. The findings of the study indicated moderate participation in user education sessions. The correlation analysis revealed that the extent of students’ participation in library user education has a substantially strong linear positive relationship in the assessment of university libraries in Meru County (p-value < 0.05, r=0.740). The study concludes that library user education significantly enhances student perception of library services. The study recommends the university library managers to aggressively integrate thorough, interesting, and easily available library user education programs into the general student orientation and academic development projects.